Neighbourhood schools & unfavourable reputation : an examination of Singapore's meritocratic education and its consequences on parental choice of school - Janathul Firdous d/o Mohamud Ali (2013)
This study examines Singapore’s promise of a meritocratic education system through the lens of the neighbourhood secondary schools. Through this analysis, it highlights the unintended consequences of the meritocratic education system namely ‘Tracking’ and the formation of an academic hierarchy. It further expands to show how an unfavourable reputation for the neighbourhood secondary schools is formed through this academic hierarchy. Then after, the underlying reason for an unfavourable reputation among parents is analyzed using the ‘Symbolic Interactionism’ Approach and ‘Labeling Theory’.